2001
DOI: 10.1016/s0043-1354(00)00296-7
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Mechanism of Salt Solution-Extracted Active Component in Moringa oleifera Seeds

Abstract: This study focuses on the coagulation mechanism by the purified coagulant solution (MOC-SC-PC) with the coagulation active component extracted from M. oleifera seeds using salt solution. The addition of MOC-SC-PC tap water formed insoluble matters. This formation was responsible for kaolin coagulation. On the other hand, insoluble matters were not formed when the MOC-SC-PC was added into distilled water. The formation was affected by Ca2+ or other bivalent cations which may connect each molecule of the active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
100
1
14

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(125 citation statements)
references
References 16 publications
10
100
1
14
Order By: Relevance
“…Measured sludge volumes generated with alum dosed alone is almost three times that of using M. oleifera alone ( Table 2). This is in agreement with other studies that have reported M. oleifera sludge production being significantly less (by a factor of up to 5) than that produced by alum [12]. In this study, sludge produced while using the combination of M. oleifera and alum was approximately half that of alum when used as the sole coagulant.…”
Section: Observations From Treatment Studiessupporting
confidence: 93%
See 2 more Smart Citations
“…Measured sludge volumes generated with alum dosed alone is almost three times that of using M. oleifera alone ( Table 2). This is in agreement with other studies that have reported M. oleifera sludge production being significantly less (by a factor of up to 5) than that produced by alum [12]. In this study, sludge produced while using the combination of M. oleifera and alum was approximately half that of alum when used as the sole coagulant.…”
Section: Observations From Treatment Studiessupporting
confidence: 93%
“…Many parts of the tree are used as traditional medicines, the seeds contain up to 40% by weight of quality edible oil (greater than 80% unsaturated fatty acid content [2]) and the seeds (and oil free presscake) yield proteins capable of acting as effective coagulants in water and wastewater treatment. The active components of the M. oleifera seeds have been determined to be cationic peptides of relatively low molecular weight (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) with an isoelectric pH value of 10 [3,4]. M. oleifera leaves are currently the focus of several development projects promoting their use as a valuable nutritional source for human consumption and to some extent as animal feed supplements [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The kernels were grounded in a coffee grinder to become particles of about 300 μm, stored at room temperature in an airtight container and used for one month (Katayon et al, 2006). To extract the active proteins, 5 g of the seed powder was suspended in 100 mL of 1.0 mol/L NaCl solution and the suspension was stirred using a magnetic stirrer for 30 min (Okuda et al, 2001). The solution was then filtered through a glass microfiber filter of 0.45 μm pore size (Whatman GF/C, UK) and the filtrate was used as the ZP adjuster.…”
Section: Mo Chitosan Soil and Modification Processmentioning
confidence: 99%
“…In recent years, there have been intense interests in the application of plant based coagulant in water and wastewater treatment [13]- [16]. A typical precursor is Detarium microcarpum seed.…”
Section: Introductionmentioning
confidence: 99%